A STUDY ON ICT-USED BY THE TEACHERS OF MTs DARUL HIKMAH BOARDING SCHOOL PEKANBARU - Linda Riana; Hadriana Hadriana; Jismulatif Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive study aims to discuss to what extent the teachers of MTs Darul Hikmah Boarding School Pekanbaru use ICT in their teaching and learning activities. The researcher used purposive technique sampling to determine the sample. The samples were 50 teachers. The data were gathered by distributing a set of questionnaire which design in the form of five points of the Likert scale. The data were analyzed using Microsoft Excel 2010. After analyzed the data, it can be revealed that the use of ICT by the teachers of MTs Darul Hikmah Boarding School Pekanbaru in their teaching and learning activities in general was in mediocre level category, with mean of 2.99. Specifically, the use of ICT by the teachers for class preparation was in mediocre level category, with the mean score of 3.14. Furthermore, the use of ICT by the teachers during teaching and learning process was in low level category, with the mean score of 2.60. Then, the use of ICT by the teachers as assessment was in high level category, with the mean score of 3.42.Keywords: A Study, ICT, teaching and learning activities